The long-term impact of refugees on labor market: Evidence from Syrian refugees in Turkey - Akyol, Zeki (Graduate School, 2023)
In this thesis, I examined the effect of Syrian refugees, who were forced to migrate to Turkey when the Syrian Civil War broke out in 2011, on the Turkish labor market through the real wages of native workers. My empirical methodology employs the staggered difference-in-differences approach. As this method is relatively new, I also provide a brief summary of recent advancements in the econometric literature. My main contribution to the existing labor economics literature is the application of recent, specifically the difference-in-differences, literature to the Syrian refugee case in Turkey. Additionally, I conduct heterogeneity analysis for each gender, sector of work, formality of work, and education level. Finally, I conclude the analysis with regional heterogeneity analysis. In addition, I investigate not only the average effects but also the long-term and cohort-specific effects of Syrian refugees on the Turkish labor market. I used the Turkish Household Labor Force dataset spanning from 2009 to 2019. The results indicate that in all NUTS-2 regions in Turkey, Syrian refugees do not have a statistically significant effect on native real wages, whereas they led to an increase of 4.7% in the real wages of natives in the East and Southeast NUTS-2 regions in Turkey. Syrian refugees significantly decreased native real wages in the informal sector by 4.98% in all NUTS-2 regions in Turkey, but they did not affect formal sector real wages in those regions. The most significant decrease in native real wages occurred in the agriculture sector in the East and Southeast NUTS-2 regions, with a drop of 33.12%. However, other sectors such as industry, construction, and services were not significantly affected by Syrian refugees. Finally, in all NUTS-2 regions in Turkey, Syrian refugees in the informal construction sector led to a decrease of 6.2% in native real wages. However, the formal construction sector, formal industry sector, and informal industry sector were not affected in the same region.
Mültecilerin işgücü piyasası üzerindeki uzun vadeli etkisi: Türkiye'deki Suriyeli mülteciler örneği
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: forced emigration; zorunlu göç; economy; ekonomi; refugees; mülteciler